Characterizing Students Through Religious Culture at Madrasah Aliyah Negeri 3 Banyuwangi - Ulum, Mohammad Bahrul (Journal of Islamic Education Research, 2022)
This age is a time for parents to educate their children by instilling good character values in the home, community, and school environment because children are very influential regarding character with their peers. Therefore, characteristics are essential for students to have a good personality found in the future. So this study aims to shape the student's character through a religious culture. This study aims to describe the formation of honest, disciplined, and socially caring students' character at Madrasah Aliyah Negeri 3 Banyuwangi. This research uses qualitative research methods with the type of case study research using descriptive data analysis. The results in this study indicate that the formation of student character through religious culture, namely honesty, disciplined, and social has resulted in good changes under the goals of educators in Madrasah Aliyah Negeri 3 Banyuwangi.